Pre-peritoneal pelvic packing for early hemorrhage control reduces mortality compared to resuscitative endovascular balloon occlusion of the aorta in severe blunt pelvic trauma patients: A nationwide analysis. Issue 8 (August 2020) - Mikdad, Sarah; van Erp, Inge A.M.; Moheb, Mohamad El; Fawley, Jason; Saillant, Noelle; King, David R.; Kaafarani, Haytham M.A.; Velmahos, George; Mendoza, April E.
Highlights: Following blunt pelvic trauma, REBOA was associated with increased mortality compared to pre- peritoneal packing (PPP). Patients undergoing REBOA placement had a shorter ICU and hospital length of stay compared to PPP. There was no difference in major postoperative complications between the two procedures. Abstract: Background: Early hemorrhage control after severe blunt pelvic trauma is life-saving. The aim of this study is to compare the efficacy and outcomes of pre-peritoneal packing (PPP) and Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) with a subsequent hemorrhage control procedure to control life-threatening pelvic hemorrhage in trauma patients. Methods: A 3-year (2015–2017) retrospective analysis of the Trauma Quality Improvement Program (TQIP) was performed. All blunt trauma patients (aged ≥15 years) who underwent PPP or Zone 3 REBOA placement were included while deaths on arrival and transfers were excluded. Patients were matched on clinical characteristics using propensity score matching (PSM). Univariate analysis was performed to compare mortality, time to procedure, time in ED, transfusion requirements, complications rates, and ICU and hospital length of stay (LOS) amongst patient groups. Results: Of 420 trauma patients, 307 underwent PPP and 113 REBOA. Patients had similar hemodynamics and ISS upon presentation, but PPP patients had a higher GCS ( P = 0.037) and more blunt kidney injuries ( P = 0.015). After PSM, 206 trauma patients were included in the analysis. There were no significant differences in blood transfusion, LOS, or major complications. Time to REBOA was shorter than time to PPP (52 vs 77.5 min; P <0.001) with longer time in ED (65 vs 51 min; p = 0.023). The 24-hour (32.4 vs 17.7%; P = 0.23) and in-hospital mortality (52.0 vs 37.3%; P = 0.048) were higher after REBOA. Conclusion: PPP is associated with improved survival compared to REBOA placement. Delay in definitive hemorrhage control may provide a potential explanation, but causation remains unresolved. This data suggests that early PPP may offer a benefit over REBOA in the setting of hemorrhage after blunt pelvic trauma. Further, large, multi-institutional studies are warranted to support these findings. Level of Evidence: Prognostic study, level III.